Ablation Resolution in Laser Corneal Refractive Surgery: The Dual Fluence Concept of the AMARIS Platform. (26th July 2010) - Arba-Mosquera, Samuel; Hollerbach, Thomas
Abstract : Purpose . To evaluate to which extent individual Zernike terms can be corrected. Methods. Ablation time and fidelity was analysed using different fluence levels (range 90–2000 mJ/cm 2 ) and aspheric ablation profiles. With optimal parameters, the extent to which individual Zernike modes can be corrected was evaluated. Results . The range 188–565 mJ/cm 2 resulted as optimum fluence level with an optimum proportion range 50%–90% for high fluence. With optimal parameters, it corresponds to 2.4 s/D at 6 mm OZ, with fidelity variance of 53 μ m RMS, and average ablation error of 0.5 μ m for each location. Ablation simulation of coma Z[3, ± 1] showed 98, 4% accuracy and 98% fit quality; trefoil Z[3, ± 3], 99, 9% accuracy and 98% fit quality; spherical aberration Z[4, 0], 96, 6% accuracy and 97% fit quality; secondary astigmatism Z[4, ± 2], 97, 9% accuracy and 98% fit quality. Real ablation on a flat plate of PMMA of coma Z[3, ± 1] showed 96, 7% accuracy and 96% fit quality; trefoil Z[3, ± 3], 97, 1% accuracy and 96% fit quality; spherical aberration Z[4, 0], with 93, 9% accuracy and 90% fit quality; secondary astigmatism Z[4, ± 2], with 96, 0% accuracy and 96% fit quality. Conclusions . Ablation of aspherical and customised shapes based upon Zernike polynomials up to the the 8th order seems accurate using the dual fluence concept implemented at the AMARIS platform.